Intact glucose uptake despite deteriorating signaling in adipocytes with high-fat feeding. (April 2018) - Hansson, Björn; Wasserstrom, Sebastian; Morén, Björn; Periwal, Vipul; Vikman, Petter; Cushman, Samuel W; Göransson, Olga; Storm, Petter; Stenkula, Karin G
Abstract : To capture immediate cellular changes during diet-induced expansion of adipocyte cell volume and number, we characterized mature adipocytes during a short-term high-fat diet (HFD) intervention. Male C57BL6/J mice were fed chow diet, and then switched to HFD for 2, 4, 6 or 14 days. Systemic glucose clearance was assessed by glucose tolerance test. Adipose tissue was dissected for RNA-seq and cell size distribution analysis using coulter counting. Insulin response in isolated adipocytes was monitored by glucose uptake assay and Western blotting, and confocal microscopy was used to assess autophagic activity. Switching to HFD was accompanied by an immediate adipocyte size expansion and onset of systemic insulin resistance already after two days, followed by recruitment of new adipocytes. Despite an initially increased non-stimulated and preserved insulin-stimulated glucose uptake, we observed a decreased phosphorylation of insulin receptor substrate-1 (IRS-1) and protein kinase B (PKB). After 14 days of HFD, both the insulin-stimulated phosphorylation of Akt substrate of 160 kDa (AS160) and glucose uptake was blunted. RNA-seq analysis of adipose tissue revealed transient changes in gene expression at day four, including highly significant upregulation of Trp53inp, previously demonstrated to be involved in autophagy. We confirmed increased autophagy, measured as an increased density of LC3-positive puncta and decreased p62 expression after 14 days of HFD. In conclusion, HFD rapidly induced systemic insulin resistance, whereas insulin-stimulated glucose uptake remained intact throughout 6 days of HFD feeding. We also identified autophagy as an early cellular process that potentially influences adipocyte function upon switching to HFD.